2020
DOI: 10.1088/1361-6382/ab778f
|View full text |Cite
|
Sign up to set email alerts
|

Canonical analysis of field theories in the presence of boundaries: Maxwell + Pontryagin

Abstract: We study the canonical Hamiltonian analysis of gauge theories in the presence of boundaries. While the implementation of Dirac's program in the presence of boundaries, as put forward by Regge and Teitelboim, is not new, there are some instances in which this formalism is incomplete. Here we propose an extension to the Dirac formalism -together with the Regge-Teitelboim strategy,-that includes generic cases of field theories. We see that there are two possible scenarios, one where there is no contribution from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Furthermore, this manuscript can be seen as a continuation of the work on gauge theories defined in regions with boundaries, following the ideas of [15,35]. There it was shown that when the action contains a boundary contribution with a time derivative, then a boundary contribution to the symplectic structure arises rather naturally.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…Furthermore, this manuscript can be seen as a continuation of the work on gauge theories defined in regions with boundaries, following the ideas of [15,35]. There it was shown that when the action contains a boundary contribution with a time derivative, then a boundary contribution to the symplectic structure arises rather naturally.…”
Section: Introductionmentioning
confidence: 89%
“…It has three parts. In the first one, we briefly summarize the formalism of gauge theories in the presence of a boundary as developed in [15]. In the second one, we summarize the isolated horizon boundary conditions and its main geometrical constituents.…”
Section: Preliminariesmentioning
confidence: 99%
See 2 more Smart Citations
“…with α = (κ |γ|)/2. Since we can not find all the "velocities" with these expressions 17 , we can define the following primary constraints,…”
Section: B1 Hamiltonian Analysismentioning
confidence: 99%